Piracy in the South China Sea : lessons from Gulf of Aden - Ho, Joshua (2012)
There has been a marked increase in the total number of piracy incidents against ships in Asia in 2010 compared to previous years. In terms of location, the South China Sea stood out. Can the counter-piracy actions in the Gulf of Aden be applied to the South China Sea?